Stunting Coaching Training for Midwives and Cadres about Stunting Prevention and Management in the First 1000 Days of Life - Pardosi, Maida; Hutabarat, Julietta; Surbakti, Elisabeth; Sianturi, Efendi; Pasaribu, Rina Doriana (Journal of Health Science and Medical Therapy, 2024)
Stunting is a problem of chronic malnutrition caused by a lack of nutritional intake in the past and a failure to achieve physical development as measured by height for age. This research aims to analyze the effect of stunting coaching training on the knowledge and skills of midwives and cadres. This research was conducted in Tarutung Regency. The research used a quasi-experimental method with a "Pretest-Posttest One Group Design" design. The target selection for training participants was purposive, namely midwives and cadres in stunting locus areas with the highest percentage of stunted toddlers. The sample in this study was 15 people (9 people were midwives, and 6 were health cadres). The evaluation results were analyzed using the Paired T-Test with the SPSS Version 22 application. The research results show that Training for midwives and health cadres saw an increase in the average knowledge score of 34.67, and all training participants were in the excellent knowledge category regarding stunting coaching training. The results of statistical tests using paired t-test statistics show a difference in the average knowledge of stunting coaching training participants before and after the Training with p-value = 0.001. Midwife and cadres always provide outreach in the form of information and education about stunting so that mothers with toddlers can participate or attend to listen to the outreach to motivate them to want to prevent stunting. Researchers also hope that families can provide good emotional, informational, and instrumental support to mothers to create healthy behavior and prevent stunting.